A cross-sectional study on the association between major dietary pattern and impaired fasting glucose - Shojaei-Zarghani, Sara; Fattahi, Mohammad Reza; Kazemi, Asma; Najafi, Nastaran; Safarpour, Ali Reza (Frontiers in Nutrition, 2025)
BackgroundImpaired fasting glucose (IFG) is a precursor to type 2 diabetes and is influenced by dietary factors. This cross-sectional study assessed the association between major dietary patterns and IFG in the baseline phase of PERSIAN Kavar cohort study (PKCS).MethodsThe study included 3,144 participants aged 35–70 years. After assessing dietary intakes by a food frequency questionnaire, principal component analysis was used to identify dietary patterns. Logistic regression model was applied to estimate the odds ratios (ORs) and 95% confidence intervals (CIs) for the association between dietary patterns and IFG.ResultsThree major dietary patterns were identified: healthy, Western-like, and CarnFat (Carnivorous-fat). In the fully adjusted model, individuals in the highest tertile of the healthy dietary pattern had a lower likelihood of IFG compared to those in the lowest tertile (OR = 0.68, 95% CI: 0.53–0.88). The second tertile of the healthy pattern was also associated with lower odds of IFG (OR = 0.77, 95% CI: 0.62–0.96). No significant associations were found for the Western-like and CarnFat dietary patterns.ConclusionA healthy dietary pattern characterized by high intakes of fruits, vegetables, low-fat dairy, nuts, seeds, olive oil, legumes, fish, and whole grains was associated with a lower risk of IFG. These findings highlight the importance of promoting healthy dietary patterns for the prevention of prediabetes and type 2 diabetes.